EVALUATION OF THE THREE IN ONE (3IN1) BEREAVEMENT PROGRAM IN BENGKULU CITY - Anshar Amin; Sugeng Suharto; Adityo Pratikno Ramadhan (RADJA PUBLIKA, 2026)
The 3in1 Bereavement Program initiated by the Bengkulu City Government is an innovation in population administration services that integrates the issuance of death certificates, updates to Family Cards, and renewal of electronic ID cards in a single process through a proactive service delivery mechanism. Although this program has been running since 2021 and demonstrates high effectiveness, it still operates without a formal legal foundation in the form of a Mayor's Regulation, relying solely on a Mayor's Decree. This study aims to evaluate program implementation using the Context, Input, Process, and Product (CIPP) model and identify factors contributing to delays in regulatory formalization. Using a qualitative case study approach, the research employs in-depth interviews, observations, and document analysis. Evaluation results show the program is effective across context, input, process, and product dimensions. However, delays in regulatory formalization are caused by four main factors: prioritization of responsiveness over legal certainty, limitations in legal human resources at the Department of Population and Civil Registration, complexity of regional regulation formation procedures, and weak momentum in the legislative process. The implications of the absence of formal regulation create vulnerabilities regarding program sustainability, limited accountability, and obstacles to policy replication.